2018
DOI: 10.31832/smj.360329
|View full text |Cite
|
Sign up to set email alerts
|

Erken Evre Dudak Kanserlerinde Boyuna Yaklaşım

Abstract: ÖzetAmaç: Bu çalışmanın amacı, erken evre dudak kanseri hastalarında, bekle-gör politikasının ve boyun diseksiyonununprognoz üzerindeki rolünü araştırmaktır.Yöntem: Mart 2007 -Nisan 2015 yılları arasında T1-2N0 alt dudak kanseri nedeniyle primer bölge ve boyun cerrahisi yapılan 20 hasta (5 kadın, 15 erkek; yaş ortalaması 62.64 yıl; 38-80 yaş aralığı) çalışmaya dahil edildi. Klinik özellikler, lezyonun lokalizasyonu, bölgesel lenf nodu durumu, tümör evrelemesi, cerrahi tedavi sonuçları ve patolojik inceleme ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the literature, there is no consensus concerning the approach to be used for a clinically negative neck node in patients with early grade lip tumors and the reported incidence of neck node metastases has ranged from 0% to 15% for T1 tumors and 11% to 35% for T2 tumors. [25] Occult metastasis in the early stage is often the reason for late cervical metastasis in these cases. As De Visscher et al [26] and Hosal et al [27] confirmed that the existence of late cervical metastasis is very resistant to treatment and results mostly in the patient's death in a 1-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is no consensus concerning the approach to be used for a clinically negative neck node in patients with early grade lip tumors and the reported incidence of neck node metastases has ranged from 0% to 15% for T1 tumors and 11% to 35% for T2 tumors. [25] Occult metastasis in the early stage is often the reason for late cervical metastasis in these cases. As De Visscher et al [26] and Hosal et al [27] confirmed that the existence of late cervical metastasis is very resistant to treatment and results mostly in the patient's death in a 1-year period.…”
Section: Discussionmentioning
confidence: 99%